2020
DOI: 10.1155/2020/8853196
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Phytochemical Contents and Biological Potential of Pomegranate (Punica granatum) Peel Extracts: Toward a New Opportunity for Minced Beef Meat Preservation

Abstract: Extraction of Tunisian pomegranate peels was employed with different solvents such as ethyl acetate, acetonitrile, and water. Total phenolic and flavonoids contents, antioxidant activity, and antibacterial capacity against five foodborne pathogenic bacteria were evaluated. The highest values of polyphenols (351 mg gallic acid equivalent/g), flavonoids (104 mg quercetin/g), and DPPH and ABTS inhibition were recorded in the ethyl acetate extract followed by the aqueous extract. The latter present the maximum ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 80 publications
2
8
1
Order By: Relevance
“…This finding is consistent with a previous study, which showed that bacteriocin-preserved beef products enhanced their shelf life during cold storage [48]. Similarly, phenolic compounds derived from Ephedra alata demonstrated efficacy against foodborne diseases [49]. Also, extracts from Adansonia digitata decreased APC during preservation of beef patties [29].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with a previous study, which showed that bacteriocin-preserved beef products enhanced their shelf life during cold storage [48]. Similarly, phenolic compounds derived from Ephedra alata demonstrated efficacy against foodborne diseases [49]. Also, extracts from Adansonia digitata decreased APC during preservation of beef patties [29].…”
Section: Discussionsupporting
confidence: 92%
“…In general, hydroxyl groups of phenolic compounds bind to proteins, forming complexes, which in turn inhibit protein oxidation ( Hoffman et al, 2014 ). Similar results to this study were reported by Fourati et al (2020) . Minced beef without any addition showed the lowest sulfhydryl concentration when compared with the sample added with antioxidants at 0 storage day.…”
Section: Resultssupporting
confidence: 93%
“…Of course, additional research is needed for more detailed explanation. According to Fourati et al (2020) , sulfhydryl concentration of minced beef was also significantly decreased during storage. Xu et al (2018) reported that the addition of mulberry polyphenol inhibited a decrease of sulfhydryl concentration in dried minced pork slices during the drying process and explained that phenolic compounds weaken protein oxidation in meat products.…”
Section: Resultsmentioning
confidence: 98%
“…In general, the bioactive agents act as bacteriostatic or bactericidal molecules towards microorganisms suggesting several antimicrobial mechanisms of action [35][36][37]. e antimicrobial activity of organic acids such as lactic, acetic, and citric acids and/or their salts is based on lowering the pH level of a medium or foodstuff as a mechanism of action to inhibit the microbial growth [6,[38][39][40].…”
Section: Mode Of Actionmentioning
confidence: 99%